Distribution patterns of micro- and meso-zooplankton communities in sea ice regions of Lützow-Holm Bay, East Antarctica - Ojima, Motoha; Takahashi, Kunio T.; Iida, Takahiro; Odate, Tsuneo; Fukuchi, Mitsuo (2013)
journal article